Simulations of the Collision between a Debris Stream and an Outer Dusty Torus: A Possible Channel for Forming a Fast-rise and Long-delay Radio Outburst in Tidal Disruption Events - Xiangli Lei; Qingwen Wu; Hui Li; Ya-Ping Li; Wei-Hua Lei; Xiao Fan; Jiancheng Wu; Mengye Wang; Weibo Yang (The Astrophysical Journal)
A geometrically thick dusty torus structure is believed to exist in the nuclear regions of galaxies (especially in active galactic nuclei). The debris stream from a tidal disruption event (TDE) will possibly collide with the dusty torus and produce a transient flare. We perform three-dimensional hydrodynamic simulations to model the dynamical evolution of the interaction between unbound debris and a dusty torus. During the continuous interaction, shocked material will be spilled out from the interaction region and form an outflow. We calculate the temporal evolution of synchrotron emission by assuming that the shock accelerates a fraction of electrons in the outflow into a nonthermal distribution. We find that radio emission from the debris–torus collision generates a steep-rise and slow-decline radio light curve due to the sharp edge and dense gas of the dusty torus, where the radio outburst is delayed relative to the main optical/X-ray outburst by several years or even several tens of years. We apply our model to a TDE that happened in a narrow-line Seyfert I galaxy (PS16dtm), where both the radio spectrum and the light curve can be roughly reproduced. Future high-sensitivity, wide-field-of-view radio surveys have the opportunity to detect more such radio flares.